HIV-1 Impact on Malaria Transmission: A Complex and Relevant Global Health Concern - Roberds, Ashleigh; Ferraro, Emily; Luckhart, Shirley; Stewart, V. Ann (Frontiers in Cellular and Infection Microbiology, 2021)
Malaria/HIV-1 co-infection has become a significant public health problem in the tropics where there is geographical overlap of the two diseases. It is well described that co-infection impacts clinical progression of both diseases; however, less is known about the impact of co-infection on disease transmission. Malaria transmission is dependent upon multiple critical factors, one of which is the presence and viability of the sexual-stage gametocyte. In this review, we summarize evidence surrounding gametocyte production in Plasmodium falciparum and the development factors and the consequential impact that HIV-1 has on malaria parasite transmission. Epidemiological and clinical evidence surrounding anemia, immune dysregulation, and chemotherapy as it pertains to co-infection and gametocyte transmission are reviewed. We discuss significant gaps in understanding that are often due to the biological complexities of both diseases as well as the lack of entomological data necessary to define transmission success. In particular, we highlight special epidemiological populations, such as co-infected asymptomatic gametocyte carriers, and the unique role these populations have in a future focused on malaria elimination and eradication.